Pesticide Spill Kits - Frederick M. Fishel (EDIS)
PI-159, a 3-page illustrated fact sheet by Frederick M. Fishel, describes the kits that pesticide applicators should maintain for use in the event of an accidental release of a pesticide. It lists contents for simple and more elaborate kits and general spill clean-up procedures. Published by the UF Department of Agronomy, November 2007.